THE PROJECT TO PROTECT THE TOURIST TRAIL ALONG THE CONSTANTINE RAVINE: SAFETY FOR THE NATURAL SCENIC BENEFITS OF THE TRAIL - Zoubir Mosbah (International Journal of Innovative Technologies in Social Science, 2024)
This study examines the evolution of the tourist trail since its update. It provides a detailed account of findings over time, highlighting various aspects of the route and the breathtaking views it offers of the Ravine Rock landscapes (Benfadel, 2016). Since the colonial era, the trail has faced obstacles that have affected its economic development. Its structuring has been shaped by historical events and their influence, particularly the Rèmes project. This analysis underscores the trail’s slow expansion since the end of the French colonial period (Mekki, 2018). Users express a desire to address the current shortcomings of the trail. Paradoxically, the caution required to navigate the route is one of the key attractions of natural tourism. The trail offers the chance to explore a natural monument, fostering meaningful interactions and providing vivid descriptions of its natural features. The aim of protecting and developing Constantine’s tourist trail is to introduce visitors to its rocky landscapes and the Rhumel, rekindling interest in nature-based tourism. The scenery - sometimes rustic, sometimes harsh due to the steep path’s challenges - offers an idealistic motivation to reconnect with nature. This progression enhances the appreciation of the striking beauty of the cliffs’ sheer faces.